Investigation of Private School Teachers' Perceptions on the Management of Educational Technologies Integration Processes - Gündoğdu, Ahmet Ali; Kırkıç, Kamil Arif; Kırkıç, Kamil Arif (Mehmet Akif OCAK, 2025)
This study aims to determine the perceptions of teachers working in private schools regarding technology integration management. This study used a descriptive survey method and a quantitative research model. The study group consisted of 220 private schoolteachers working in Istanbul. Demographic information form and "Teachers' Perception Scale on Technology Integration Processes" were used to collect data. The frequency and percentage distributions of the demographic information obtained from the scale were determined. Because the distribution of bivariate groups was expected, a t-test was applied to these groups. One-way analysis of variance (One-way ANOVA) was applied to three or more variables, and the "Kruskal Wallis Test" was applied to the "Type of School" variable with fewer than 30 groups. According to the results of the research, it was determined that private school teachers' perceptions of technology integration management were at an "undecided" level. It was found that private school teachers' perceptions of technology integration management did not differ significantly according to gender. However, their perceptions of technology integration management differed significantly depending on their educational status, the type of school in which they worked, and the level of use of educational technologies. In addition, the research results showed no significant difference between private school teachers' age, professional seniority, and seniority in the institution regarding their perceptions of technology integration management.
Keywords: Educational technology; Management of technology integration; Perception of teachers; Private school; Technology integration